2016
DOI: 10.18203/2394-6040.ijcmph20164720
|View full text |Cite
|
Sign up to set email alerts
|

Study of prevalence of diabetes mellitus in the rural areas of Hubballi, Karnataka, India

Abstract: Background: India is largely a rural nation. The prevalence of diabetes in the rural areas is increasing. The prevalence data is mainly available for urban areas and insufficient data is available for rural areas.  Aims and objectives: To estimate the prevalence of diabetes mellitus in rural areas of Hubli taluk, Karnataka, India and also to assess the risk factors associated.Methods: One village was selected randomly in the taluk. Information was gathered on demographics, personal history, past history, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In contrast, a separate study in rural areas of Karnataka reported a higher prevalence rate of 22%. The case burden was not decreased as significantly as it was initially intended [ 38 ]. A concurrent study spanning 15 states and published in 2017 indicated rural area diabetes prevalence rates of 7.3% and 5.2% [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, a separate study in rural areas of Karnataka reported a higher prevalence rate of 22%. The case burden was not decreased as significantly as it was initially intended [ 38 ]. A concurrent study spanning 15 states and published in 2017 indicated rural area diabetes prevalence rates of 7.3% and 5.2% [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Diabetes kills more than 80% of people in low and middle-income nations. It is India's fourth biggest cause of death, affecting 10-16 percent of urban residents and 5.33-6.36 percent of rural residents, with the number expected to increase by 2030 [1].…”
Section: Introductionmentioning
confidence: 99%